+0

0
168
3
+46

ab-c=ae+f

Solve for a

Please solve and explain this. I can't understand the concept!

Sep 28, 2018

#2
+100155
+3

Hi Curry

sorry, your question got flagged automatically, I am not sure why.

Probably the program thought those letters in your equation looked too random and it was flagged as a potential rubbish question.  These questions viewed later by a moderator and shown.

ab-c=ae+f        solve for a

The idea is to get a by itself in fron to the equal sign.

First get every term WITH an a on the left and everything eles on the right.

$$ab-c=ae+f\\ \text{subtract ae from both sides}\\ ab-c-ae=ae+f-ae\\ ab-c-ae=f\\ \text{Now add c to both sides}\\ ab-c-ae+c=f+c\\ ab-ae=f+c\\ \text{Now factor out the a on the left side}\\ a(b-e)=f+c\\ \text{Now divide both sides by (b-e)}\\ \frac{a(b-e}{b-e}=\frac{f+c}{b-e}\\ a=\frac{f+c}{b-e}\\ \\~\\ \text{You cannot divide by 0 so you should put }b-e\ne0\\\ \text{which is the same as } b\ne e$$

.
Sep 28, 2018

#1
+46
+1

why is this flagged?

Sep 28, 2018
#2
+100155
+3

Hi Curry

sorry, your question got flagged automatically, I am not sure why.

Probably the program thought those letters in your equation looked too random and it was flagged as a potential rubbish question.  These questions viewed later by a moderator and shown.

ab-c=ae+f        solve for a

The idea is to get a by itself in fron to the equal sign.

First get every term WITH an a on the left and everything eles on the right.

$$ab-c=ae+f\\ \text{subtract ae from both sides}\\ ab-c-ae=ae+f-ae\\ ab-c-ae=f\\ \text{Now add c to both sides}\\ ab-c-ae+c=f+c\\ ab-ae=f+c\\ \text{Now factor out the a on the left side}\\ a(b-e)=f+c\\ \text{Now divide both sides by (b-e)}\\ \frac{a(b-e}{b-e}=\frac{f+c}{b-e}\\ a=\frac{f+c}{b-e}\\ \\~\\ \text{You cannot divide by 0 so you should put }b-e\ne0\\\ \text{which is the same as } b\ne e$$

Melody Sep 28, 2018
#3
+46
0

Sorry I'm saying this a little late, but thank you. This really helped, and now I understand the concept

Oct 2, 2018